Model of the postural mechanisms formation in children with musculoskeletal system disorders by means of corrective physical education - Бочков, П. Н. (Scientific notes of the pedagogical department, 2019)
The article attempts to present a system model of postural mechanisms formation in children with musculoskeletal system disorders with a syndrome of postural deficiency, using the possibilities of corrective physical education. The hypothesis foundation construction of such a test model was based on the well-known assumptions of posturology about the five entrances of the postural aplomb system: three external and two internal, which integrated activity constitutes the success of the child’s body dynamic stabilization in space. Based on the phylogenetic predetermination of these inputs formation, firstly a model of sequential stimulation of external sensory inputs is proposed to form a stable body position in space (vestibular, visual, plantar), and then internal (oculomotor and proprioceptive) with parallel integration study of all discussed above sensory flows in specially organized postural modes conducted on the basis of the game (theatrical) method.